1989
DOI: 10.1111/j.1365-2044.1989.tb11348.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia in infants born prematurely

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
(5 reference statements)
0
19
0
1
Order By: Relevance
“…40 To reduce the incidence of postoperative apnea, spinal, rather than general, anesthesia has been used for inguinal hernia repair in preterm infants. [41][42][43] Although some studies have been encouraging, none have been adequately powered. Indeed, Craven et al published a Cochrane Collaboration analysis in which only 108 patients from 4 small randomized or quasi-randomized studies comparing spinal and general anesthesia were identified.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…40 To reduce the incidence of postoperative apnea, spinal, rather than general, anesthesia has been used for inguinal hernia repair in preterm infants. [41][42][43] Although some studies have been encouraging, none have been adequately powered. Indeed, Craven et al published a Cochrane Collaboration analysis in which only 108 patients from 4 small randomized or quasi-randomized studies comparing spinal and general anesthesia were identified.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…Paralysed muscles bulge outwards while unparalysed muscles contact inward during expiration with the level of anaesthesia being several dermatomes cephalad to the level of muscle relaxation [139]. Observation of the disappearance of the withdrawal response caused by tetanic stimulation from a peripheral nerve stimulator has also been used [150,151]. A variety of drugs and dosages have been described for subarachnoid anaesthesia in children ( Table 5).…”
Section: Anatomymentioning
confidence: 99%
“…Several authors have used single dose subarachnoid or caudal epidural anaesthesia in expremature babies having perineal or simple lower abdominal operations (Gallagher & Crean 1989;Gunter et al 1991;Sartorelli et al 1992). These blocks have a limited but variable duration of action which Heart rate during combined subarachnoid-epidural anaesthesia.…”
Section: Discussionmentioning
confidence: 98%